State merit aid programs and youth labor market attachment - David E. Frisvold; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2018)
This paper examines the impact of state merit-aid programs on the labor market attachment of high school-aged youths. The labor force participation rate of teenagers has fallen substantially in recent decades, coinciding with the introduction of merit-aid programs. These programs reduce the price of attending an in-state public college or university for high-achieving students and have the potential to influence students' allocation of time and effort between labor market activities, human capital development, and other forms of leisure. We examine the influence of these programs based on their generosity, both in the amount of aid provided to a recipient and the percent of students who are recipients of aid, and in their selectivity. Our results suggest that programs that are more selective reduce labor force participation, but are not a significant cause in the decline in teenage labor force participation in recent decades.
Keywords: J2; I2; 330; merit aid; labor force participation; education; financial aid